Titan Calling. - James Oberg (IEEE spectrum)
Last june, scientists were thrilled when NASA's Cassini probe successfully began orbiting Saturn after a 3.5-billion kilometer, seven-year journey across the solar system. The 6-ton spacecraft immediately started returning spectacular pictures of the planet, its rings, and its 30-plus moons. It was just the beginning of Cassini's four-year tour of Saturn's neighborhood, and while scientists expect amazing discoveries in the years to come, the most dramatic chapter in the mission's history will happen this January, when scientists attempt to peek beneath the atmospheric veil that surrounds Saturn's largest moon, Titan - a chapter that might have ended in disaster, save for one persistent engineer.